Neo-humanism and COVID-19: Opportunities for a socially and environmentally sustainable world - Francesco Sarracino; Kelsey J. O'Connor (Global Labor Organization (GLO), 2021)
A series of crises, culminating with COVID-19, shows that going "Beyond GDP" is urgently necessary. Social and environmental degradation are consequences of emphasizing GDP as a measure of progress. This degradation created the conditions for the COVID-19 pandemic and limited the efficacy of counter-measures. Additionally, rich countries did not fare the pandemic much better than poor ones. COVID-19 thrived on inequalities and a lack of cooperation. In this article we leverage on defensive growth models to explain the complex relationships between these factors, and we put forward the idea of neohumanism, a cultural movement grounded on evidence from quality-of-life studies. The movement proposes a new culture leading towards a socially and environmentally sustainable future. Specifically, neo-humanism suggests that prioritizing well-being by, for instance, promoting social relations, would benefit the environment, enable collective action to address public issues, which in turn positively affects productivity and health, among other behavioral outcomes, and thereby instills a virtuous cycle. Arguably, such a society would have been better endowed to cope with COVID-19, and possibly even prevented the pandemic. Neo-humanism proposes a world in which the well-being of people comes before the wellbeing of markets, in which promoting cooperation and social relations represents the starting point for better lives, and a peaceful and respectful coexistence with other species on Earth.
Keywords: I31; I10; P00; O10; Q50; 330; COVID-19; neo-humanism; subjective well-being; economic growth; sustainability; social capital; beyond GDP; quality of life; defensive growth; environmental degradation